2019
DOI: 10.1177/1120672119827855
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aflibercept and ranibizumab in diabetic macular edema associated with subretinal detachment

Abstract: Purpose: To compare the efficacy of ranibizumab and aflibercept in the treatment of diabetic macular edema associated with subfoveal retinal detachment. Methods: This is a retrospective, comparative study. The treatment-naïve diabetic macular edema patients who had diabetic macular edema associated with subfoveal retinal detachment and underwent intravitreal aflibercept or intravitreal ranibizumab treatment were included. The patients were treated on a pro re nata treatment regimen after a loading dose of 3-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…The former may cause complications such as vision loss or visual field defect, while the latter injection of drugs such as glucocorticoid triamcinolone acetonide has certain curative effects, but it also has many adverse reactions. Aflibercept has been used well in recent years, and comparative studies with ranibizumab are more common [ 12 , 13 ], while the comparative analysis of efficacy with triamcinolone acetonide is immature. Based on this background, the purpose of this study was to compare and analyze the efficacy of the two in the treatment of cystic macular edema, in order to contribute reasonable suggestions for the clinical treatment of DR patients.…”
Section: Discussionmentioning
confidence: 99%
“…The former may cause complications such as vision loss or visual field defect, while the latter injection of drugs such as glucocorticoid triamcinolone acetonide has certain curative effects, but it also has many adverse reactions. Aflibercept has been used well in recent years, and comparative studies with ranibizumab are more common [ 12 , 13 ], while the comparative analysis of efficacy with triamcinolone acetonide is immature. Based on this background, the purpose of this study was to compare and analyze the efficacy of the two in the treatment of cystic macular edema, in order to contribute reasonable suggestions for the clinical treatment of DR patients.…”
Section: Discussionmentioning
confidence: 99%
“…The target specificity of currently used anti-VEGF drugs might also yield some hints about the pathobiological function of VEGFR1 in DR. There are numerous studies in DME patients showing significant differences between ranibizumab and aflibercept when looking at certain clinical readouts, with aflibercept showing higher efficacy or longer lasting treatment effects ( Bhandari et al, 2020 ; Jampol et al, 2016 ; Kaldirim et al, 2019 ; Ozkaya et al, 2020 ; Sarda et al, 2020 ; Shimizu et al, 2017 ). Furthermore, comparisons between aflibercept and bevacizumab * had similar outcomes ( American Academy of Opthalmology, 2019 ; Virgili et al, 2018 ; Wells et al, 2015 ; Wells et al, 2016 ).…”
Section: Role Of Vegfr1 In Retinal Vascular Diseasementioning
confidence: 99%
“…Two studies were not included in the analyses due to missing standard deviation data; however, these studies reported no significant difference in BCVA improvement between aflibercept and ranibizumab at 12 months ( P = 0.237 20 and P = 0.8). 21 Of the six studies, two RCTs demonstrated that the overall 1-year improvement in BCVA was significantly better with aflibercept (WMD = 2.19 ETDRS letters; 95% CI: 0.25–4.12 ETDRS letters; P = 0.027, I 2 = 0.0%) [ Figure 9 ] and four non-RCTs demonstrated a 1-year improvement in BCVA which was nonsignificantly better with aflibercept compared with ranibizumab (WMD = 1.53 ETDRS letters; 95% CI: –0.05–3.11 ETDRS letters; P = 0.058, I 2 = 21.5%) [ Figure 9 ]. At 2 years, visual outcomes related to aflibercept were no longer found to be superior to ranibizumab (WMD = 1.66 ETDRS letters, 95% CI: –0.15–3.48 ETDRS letters, P = 0.072, I 2 = 48.3%) [ Figure 8 ].…”
Section: R Esultsmentioning
confidence: 99%
“…displayed similar results at 1 year ( P = 0.3). 21 Of the six studies, two RCTs demonstrated a nonsignificantly increased reduction in CMT with aflibercept compared to ranibizumab (WMD = −21.55 μm, 95% CI = −44.02–0.92 μm, P = 0.060, I 2 = 0.0%) [ Figure 13 ]. Four non-RCTs demonstrated a nonsignificantly increased reduction in CMT with aflibercept compared to ranibizumab (WMD = −10.12 μm, 95% CI = −51.71–31.47 μm, P = 0.633, I 2 = 83.6%) [ Figure 13 ].…”
Section: R Esultsmentioning
confidence: 99%
See 1 more Smart Citation